2018
DOI: 10.5505/pajes.2017.03779
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation kinetics of rutin and total phenolic compounds in rosehip (Rosa canina L) nectar

Abstract: In this research it is attempted to determine the loss of rutin and total phenolic compounds in rosehip nectar with the heating periods (0, 5, 10, 15, 20 and 30 min) at temperatures ranging from 70 to 95 °C. Spectrophotometric and liquid chromatographic (HPLC) methods were used to determine the concentrations of total phenolic compounds and rutin, respectively. Thermal degradations of TPC and rutin in rosehip nectar were fitted to a first-order reaction kinetic model. Arrhenius relationship was used in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…The decrease of total phenolic content due to the thermal treatment was also stated by Kadakal and Duman [62] who showed a thermal degradation of rutin and total phenolic compounds during nectar manufacturing using rose hip. A temperature higher than 70 • C caused a higher degradation rate of the compounds.…”
Section: Phenolic Acid Content Of Mixtures and Extrudatessupporting
confidence: 67%
“…The decrease of total phenolic content due to the thermal treatment was also stated by Kadakal and Duman [62] who showed a thermal degradation of rutin and total phenolic compounds during nectar manufacturing using rose hip. A temperature higher than 70 • C caused a higher degradation rate of the compounds.…”
Section: Phenolic Acid Content Of Mixtures and Extrudatessupporting
confidence: 67%
“…It was obvious that this increment caused a decrement in the values of t 1/2 and D. Rate constant of TPC thermal degradation ranged from 0.0332 to 0.0775 h −1 . Akdaş and Başlar (2015), Sarpong et al (2018), and Kadakal and Duman (2018) have reported an increment in TPC thermal degradation in different foods with an increase in temperature. TPC thermal degradation was slightly affected by 10°C temperature increment.…”
Section: Kinetic Parameters Of Tpc and Acmentioning
confidence: 96%
“…Quotient indicator ( Q 10 ) is another technique used to express the dependence of the reaction rate on temperature in such a way that the reaction rate is changed when the temperature is increased by 10°C (Kadakal & Duman, 2018; Van Boekel, 2008):Q10=)(k2k110T2T1,where T is the temperature in Celsius, k1 and k2 are the rate constants of HMF formation which is chosen according to best kinetic model at temperatures of T1 and T2 respectively.…”
Section: Methodsmentioning
confidence: 99%